Court-annexed mediation fair and speedy administration of justice in the Philippines. - Baes, Marty Vergel
The Philippine Judicial System experiences a problem characterized by clogged court dockets. Courts are having a hard time in resolving the cases brought before them. court-annexed mediation (CAM) was adopted to supplement the traditional due process (DPL) method of resolving cases. To understand how CAM speeds up the administration of justice, the CAM and DPL method was compared to determine the difference in the length of time and the amount of resources spent for case resolution. Interviews, archival research, and participant observations was conducted. The results revealed that CAM resolve cases in a short period of time involving lesser amount of resources spent compared to the DPL, method. Though CAM proves to be a speedy and expedient method of case resolution, it is not yet able to solve the problem of clogged court dockets for the reason that it is still a new method of resolving cases.